Is differential cleaning needed for SARS-CoV-2 beyond standard procedures? A systematic review - Uduak Okomo; Ememobong N. Aquaisua; Osamagbe Asemota; Deborah Ndukwu; Josephine E. Egbung; Ekpereonne B. Esu; Olabisi A. Oduwole; John E. Ehiri (Journal of Public Health in Africa)
Background: There is a substantial risk of indirect transmission of SARS-CoV-2 from contaminated surfaces and objects in healthcare settings.